2006
DOI: 10.1111/j.1365-2567.2006.02403.x
|View full text |Cite
|
Sign up to set email alerts
|

The lack of RNA‐dependent protein kinase enhances susceptibility of mice to genital herpes simplex virus type 2 infection

Abstract: Summary Mice deficient in RNA‐dependent protein kinase (PKR–/–) or deficient in PKR and a functional 2′,5′‐oligoadenylate synthetase (OAS) pathway (PKR/RL–/–) are more susceptible to genital herpes simplex virus type 2 (HSV‐2) infection than wild‐type mice or mice that are deficient only in a functional OAS pathway (RL–/–) as measured by survival over 30 days. The increase in susceptibility correlated with an increase in virus titre recovered from vaginal tissue or brainstem of infected mice during acute infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…Variation was present even between mice from the same litters that that were given HSV-2 on the same day. Other published studies also have reported intra-experiment variability in pathology and time to death of HSV-2 infection [36, 37]. Thus, variability in HSV-2 infection could account for some of the variation in HIV infection observed in our study.…”
Section: Discussionsupporting
confidence: 69%
“…Variation was present even between mice from the same litters that that were given HSV-2 on the same day. Other published studies also have reported intra-experiment variability in pathology and time to death of HSV-2 infection [36, 37]. Thus, variability in HSV-2 infection could account for some of the variation in HIV infection observed in our study.…”
Section: Discussionsupporting
confidence: 69%
“…Next, we asked whether the alterations in the behavioral components of sickness of PKR−/− mice would be correlated with exaggerated bacterial load. It has been well reported that loss of PKR can often enhance viral replication [ 41 , 44 , 101 , 102 ]. Another study has shown that PKR is involved in resistance to Toxoplasma gondii [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that mice deficient in RNase L, PKR, or both have a range of pathogenic phenotypes in response to numerous viruses. The viruses tested in these mice include encephalomyocarditis virus [ 31 , 32 ] vesicular stomatitis virus [ 33 , 34 , 35 ], herpes simplex virus types 1 and 2 [ 36 , 37 , 38 ], coxsackievirus B4 [ 39 ], West Nile virus [ 40 ], murine coronavirus [ 41 ], and vaccinia virus [ 42 ]. Depending on the study, pathogenic outcomes for many of these viruses typically include increased mortality, higher viremia and/or viral burden in various tissues, and accelerated onset of clinical disease.…”
Section: Ifn Responses and Isgs In Viral Pathogenesismentioning
confidence: 99%